A High-Throughput Small Molecule Screen Identifies Ouabain as Synergistic with miR-34a in Killing Lung Cancer Cells - Rupaimoole, Rajesha (iScience, 2020)
MicroRNA-34 (miR-34) is one of the major families of tumor suppressor miRNAs often lost in cancers. Delivery of miR-34a mimics to affected tumors as a therapeutic strategy has been tried in pre-clinical studies and in a phase I clinical trial. One approach to increase efficacy and reduce toxicity is to rationally identify drug combinations with small molecules that synergize with miR-34a. In this study we performed a high-throughput screen of a large panel of small molecules with known biological activity and identified ouabain as a candidate small molecule that synergized with miR-34a in killing lung cancer cells. We elucidated autophagy activation as a key mechanism by which miR-34a and ouabain causes increased cytotoxicity in cells. We posit that this combinatorial approach could reduce the active dose of miR-34a needed in vivo to observe tumor shrinkage and potentiate the development of miR-34a combination therapies in the future.